Grass : In Search of Human Habitat - Truett, Joe C. (Joe Clyde), 1941- (Book collections on Project MUSE., 2010)
Part autobiography, part philosophical rumination, this evocative conservation odyssey explores the deep affinities between humans and our original habitat: grasslands. In a richly drawn, anecdotally driven narrative, Joe C. Truett, a grasslands ecologist who writes with a flair for language, traces the evolutionary, historical, and cultural forces that have reshaped North American rangelands over the past two centuries. He introduces an intriguing cast of characters-wildlife and grasslands biologists, archaeologists, ranchers, and petroleum geologists-to illuminate a wide range of related top.